An Analysis of External Debt and Capital Flight in the Severely Indebted Low Income Countries in Sub-Saharan Africa - Ajayi, Simeon (IMF Working Papers; Working Paper ;, 1997)
The general objective of this study is to analyze the external debt and debt burdens of the severely indebted sub-Saharan African countries, estimate the magnitude of capital flight from them, and relate the estimate of capital flight to some macroeconomic aggregates. The study also contains policy implications of international efforts to deal with the high levels of external debt in sub-Saharan Africa in conditions of extreme poverty, and stagnant and declining exports. It questions the theoretical foundation in which the external debt strategy has been based and offers solutions to the external debt problem.